A case of ALK-positive anaplastic large cell lymphoma - a cutaneous or systemic variant? - Jankowska-Konsur, Alina; Maj, Joanna; Kuczborska, Iwona; Mazur, Grzegorz (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Anaplastic large cell lymphoma is a lymphoproliferative disorder with primary or secondary skin involvement. Objective. Presentation of a patient with skin lesions in the course of anaplastic large cell lymphoma with expression of ALK, a marker of systemic disease, without internal organ involvement. Case report. A 55-year old woman was referred to the hospital with erythematous, infiltrative, partially ulcerating skin lesions, developing for 4 months on the trunk and extremities. On the basis of skin biopsy CD30 positive anaplastic large cell lymphoma was diagnosed. Imaging analysis did not reveal any lymphoma infiltrations in the internal organs and lymph nodes. In the treatment a chemotherapy regimen (CHOP) was administered with complete remission in the 7-month follow-up. Conclusions. ALK expression is a characteristic feature of systemic anaplastic large cell lymphoma. Despite early diagnosis and no internal organ involvement, uncertain prognosis of the disease requires intensive therapy.